The potential of chitosan-based film with curry leaf essential oil as natural insect-repellent food packaging - R., Nur Fatin Nazurah; M. A., Noranizan; M.A.R., Nor Khaizura; Z. A., Nur Hanani (Elsevier, 2022)
This research investigated the effect of curry leaf essential oil (CLEO) on the properties of chitosan-based film and its potential as a natural insect-repellent film. CLEO was added at different concentrations (0.5–1.5 %) with Tween 80 (0.1–0.3 %) as a surfactant. Chitosan-CLEO matrix films successfully reduced (p < 0.05) the moisture content, film water solubility and water vapor permeability values. The incorporation of Tween 80 at 0.3 % (of distilled water) further improved (p < 0.05) the film's moisture and water barrier. Films containing more CLEO showed higher total phenolic compound and antioxidant activity with the DPPH (2, 2-diphenyl-1-picrylhydrazyl) % increased significantly (p < 0.05) from 19.07 % to 33.67 %. The chitosan-CLEO film-forming emulsion (FFE) also inhibited the Gram-positive bacteria (Staphylococcus aureus and Listeria monocytogenes) and Gram-negative bacteria (Escherichia coli and Salmonella typhimurium), indicating the potential of CLEO as antibacterial agents. Meanwhile, chitosan film incorporated with 0.5 % CLEO successfully repelled at least 60–70 % of Musca domestica in the area preference test, while the films enriched with 1.0 % CLEO and 0.3 % Tween 80 showed 100 % repellency. Repellency results are considered very promising for chitosan-CLEO films to develop as active packaging with a natural repellent effect.